1997
DOI: 10.1055/s-2006-957691
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effect of Seishin-kanro-to in KK-Ay Mice

Abstract: The hypoglycemic effect of Seishin-kanro-to (SK) was investigated in KK-Ay mice, one of the non-insulin dependent diabetic mellitus types. SK (1700 mg/kg) reduced the blood glucose of KK-Ay mice from 557 +/- 17 to 383 +/- 36 mg/100 ml 7 hours after single oral administration (P < 0.001). SK also decreased the blood glucose and improved glucose tolerance 5 weeks after repeated administration in KK-Ay mice. These results support, therefore, the use of SK in patients with diabetes and confirm its role as a tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Radix Rehmanniae was described to have hypoglycemic effects from traditional practice of Chinese medicine, and was also observed from some other scientific research studies (Kiho et al, 1992;Miura et al, 1997). However, in this study, RR extract was only associated with a drop of plasma glucose at one time point after single treatment, probably due to the fact that time is required for the digestion and absorption of RR.…”
Section: Discussionmentioning
confidence: 48%
“…Radix Rehmanniae was described to have hypoglycemic effects from traditional practice of Chinese medicine, and was also observed from some other scientific research studies (Kiho et al, 1992;Miura et al, 1997). However, in this study, RR extract was only associated with a drop of plasma glucose at one time point after single treatment, probably due to the fact that time is required for the digestion and absorption of RR.…”
Section: Discussionmentioning
confidence: 48%
“…Indeed, studies have shown that SJH has hypoglycemic effects [21,48]. The water extract of Rehmannia glutinosa Libosch.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, RA has been used in inflammation control and prevention of insulin resistance [15,16] , and RR has been shown to elicit antihyperglycemic and anti-inflammatory effects [17][18][19][20][21] . However, the direct effects of RA and RR on diabetic foot ulcer have not been studied.…”
Section: Introductionmentioning
confidence: 99%